Applying a dual process model of self-regulation: The association between executive working memory capacity, negative urgency, and negative mood induction on pre-potent response inhibition - Gunn, Rachel L.; Finn, Peter R. (Personality and individual differences, 2015)
•High NU was significantly associated with lower eWMC.•Low eWMC predicted more false alarms on the cued go/no-go task.•A significant interaction between high NU and low eWMC predicted more false alarms.•Combined cognitive and emotional load did not significantly increase false alarms. This study tested a dual-process model of self-control where the combination of high impulsivity (negative urgency – NU), weak reflective/control processes (low executive working memory capacity – E-WMC), and a cognitive load is associated with increased failures to inhibit pre-potent responses on a cued go/no-go task. Using a within-subjects design, a cognitive load with and without negative emotional load was implemented to consider situational factors. Results suggested that: (1) high NU was associated with low E-WMC; (2) low E-WMC significantly predicted more inhibitory control failures across tasks; and (3) there was a significant interaction of E-WMC and NU, revealing those with low E-WMC and high NU had the highest rates of inhibitory control failures on all conditions of the task. In conclusion, results suggest that while E-WMC is a strong independent predictor of inhibitory control, NU provides additional information for vulnerability to problems associated with self-regulation.